PRAKTIK JUAL BELI BERBASIS INFORMATIKA DAN TRANSAKSI ELEKTRONIK PERSPEKTIF UU NO 19 TAHUN 2016 DAN HUKUM EKONOMI SYARIAH - Billah, Akrim (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2023)
Law No. 19 of 2016 regulates the regulation of legal legality of buying and selling based on information and electronic transactions supported by the law on consumer protection in 1999 and trade law no. 14. Likewise, Sharia Economic Law regulates all forms of activities both fertically and horizontally, the existence of Sharia Economic Law as the main reference becomes the benchmark in both social and digital muamalah. 4.0 is an era where the digital world dominates all "economic" activities, digital developments in the 4.0 era make the world in one hand, especially in the world of online buying and selling. From internal and external cities can easily interact through the online media. With the development of information technology has caused world relations to become borderless and caused changes in economic matters quickly, thus buying and selling transactions can be carried out through electronic transactions that are not limited by place and time. The research method used is juridical narrative, while the data collection method uses primary, secondary, and tertiary legal materials. The purpose of this study is to explain how the views of Law No. 19 of 2016 and Sharia Economic Law on the practice of buying and selling based on information and electronic transactions.